The relationship between vibrotactile perception and chemical exposure among vehicle service technicians in Klang Valley, Malaysia - Mohd Tamrin, Shamsul Bahri; Zali, Nurul Ain; Karuppiah, Karmegam (Tehran University of Medical Sciences, 2016)
Background: Hazardous chemicals, which give detrimental effect to the central nervous system, are widely used in the vehicle services industry. The use of Vibrotactile Perception Threshold (VPT) as a screening tool for chemical exposure is new in developing country such as Malaysia. Therefore, this study determined the relationship between VPT and chemical exposure among vehicle service technicians in Klang Valley.